2015
DOI: 10.1186/s13256-014-0505-4
|View full text |Cite
|
Sign up to set email alerts
|

Massive malignant solitary fibrous tumor arising from the bladder serosa: a case report

Abstract: IntroductionSolitary fibrous tumors are rare neoplasms of mesenchymal origin. They are often of low malignant potential and rarely metastasize. While they frequently arise from the pleura, they can occur at any soft tissue site in the body. We present a case of a large (28 × 21cm) malignant solitary fibrous tumor arising from the bladder serosa. In addition, the clinicopathologic features, differential diagnosis, cytogenetics and management of this rare disease are discussed, along with a review of the existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
2
16
0
1
Order By: Relevance
“…[12][13][14][15][16] Sometimes, a diagnosis of malignant soft tissue tumor was considered. Actual malignant bladder SFT has been described, [7] while to the best of our knowledge, this is the first case of a SFT of just 4 mm.…”
Section: Discussionmentioning
confidence: 76%
“…[12][13][14][15][16] Sometimes, a diagnosis of malignant soft tissue tumor was considered. Actual malignant bladder SFT has been described, [7] while to the best of our knowledge, this is the first case of a SFT of just 4 mm.…”
Section: Discussionmentioning
confidence: 76%
“…The third case in this study (case 9) showed a rapid recurrence after 12 months. This behaviour may relate to proposed mechanistic pathways for development of a malignant solitary fibrous tumour involving dedifferentiation of a pre-existing benign tumour and acquisition of additional complex genetic aberrations 32 33. As in other sites, studies are currently expanding the understanding of other genes overexpressed in solitary fibrous tumours, which may lead to insight into the mechanisms of progression and insight into subsequent therapeutic targets 9 32–34…”
Section: Discussionmentioning
confidence: 99%
“…[1] SFT can be found in many parts of the body and generally appears in the visceral pleura. Additionally, SFT is also observed in the head and neck region, [2] bones, [3,4] breasts, [5] the abdominal pelvic cavity, [6] and retroperitoneum. However, SFT arising from the seminal vesicle is exceedingly rare.…”
Section: Introductionmentioning
confidence: 99%